Pengembangan Media Pembelajaran Articulate Storyline 3 Berbasis Problem Based Learning (PBL) Pada Pembelajaran IPAS Kelas V Sekolah Dasar - Windy Wulan Septina; Yeni Erita (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The purpose of this research is to create educational media using Articulate Storyline 3 that is legitimate, usable, and successful. This study is an example of R&D using the ADDIE development paradigm. Steps one through five make up the ADDIE model: analysis, planning, development, execution, and assessment. This study's data underwent evaluations for validity, practicality, and efficacy. Before moving on to Bandar Buat and Indarung, the trial research subjects were located at SD Negeri 11 Indarung. A mean score of 91.33% places the findings in the "Very Valid" category, indicating high validity. The trial school's practicality results were 88.92% in the "Very Practical" category. At the same time, SD Negeri 01 Bandar Buat researchers achieved a 95.18 percent success rate in the "Very Practical" category, while SD Negeri 21 researchers achieved a 93.26 percent success rate in the same area. A score of 85.71% was achieved on the effectiveness test at the trial school. At the same time, SD Negeri 21 Bandar Buat's research school achieved a percentage of 93.75% and SD Negeri 01 Bandar Buat's research school achieved an effectiveness result of 86.95%. The usage of Articulate Storyline 3 as a teaching tool in fifth grade science at the elementary school level has thus been deemed legitimate, feasible, and effective.